Analisi Penetapan Harga Sembako Di Dusun Blokagung Dalam Persfektif Ekonomi Islam - Suprapto, Ribut; Mamlukhah, Mamlukhah; Mawaddah, Nila Rizqina (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
Pricing is a method used by grocery store traders to seek profits. The research in this scientific work aims to find out how basic food prices are determined in Blokagung Hamlet, and whether the price setting process is in accordance with the price concept in Islamic economics. This research is qualitative field research, namely obtaining data from direct field research regarding the determination of basic food prices in Blokagung Hamlet. The results of this research found that price determination in buying and selling basic necessities is based on the prices prevailing on the market and the prices prevailing at that time, then what differentiates prices between traders is where the supply comes from. The review of Islamic law regarding price differences in buying and selling basic necessities in Blokagung Hamlet as a whole is in accordance with the concept of price in Islam, for harmony and the conditions for buying and selling have also been fulfilled. Traders are also able to practice as taught by the Prophet Muhammad in trading.